2019
DOI: 10.1021/acs.analchem.8b05845
|View full text |Cite
|
Sign up to set email alerts
|

HPLC–UV–MS Analysis: A Source for Severe Oxidation Artifacts

Abstract: HPLC coupled to both UV and MS is an established setup for purity assessments in many areas. With evolving technology, instrument sensitivity increases, calling for lower sample concentration, while light flux in a commercial UV detector cell is considerably higher than earlier. This evolution has now reached the point where radicals formed by UV light are abundant enough, compared to the analyte levels, to generate unwanted artifact signals in the MS spectrum. In this work we show several examples from pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Artificial oxidation can occur under normal operating conditions dependent on the field strength and the flow rate of the solution passing through the electrospray capillary 6 or as a result of gradual corrosion of stainless steel electrospray emitters 7 . Moreover, radicals formed by the light of UV detectors employed in online‐chromatography can generate unwanted artifact signals in the mass spectrum as well 8 …”
Section: What Is the Problem? Critical Observationsmentioning
confidence: 99%
“…Artificial oxidation can occur under normal operating conditions dependent on the field strength and the flow rate of the solution passing through the electrospray capillary 6 or as a result of gradual corrosion of stainless steel electrospray emitters 7 . Moreover, radicals formed by the light of UV detectors employed in online‐chromatography can generate unwanted artifact signals in the mass spectrum as well 8 …”
Section: What Is the Problem? Critical Observationsmentioning
confidence: 99%
“…In applications where the spectroscopic properties of the amino acid residues are applied, for example, detection in chromatography, UV wavelengths are used. During these kinds of exposure, the molecules may suffer from oxidation, misfolding, and aggregation, which can be detected as abundant artifacts in analysis or, in the case of light-stressed IgG1, cause immunogenic response. Understanding the interaction between UV light and amino acid polymers can therefore help unravel the photoprocesses that occur to important proteins in vivo and increased understanding of the photochemical reactions can aid the design of more stable biopharmaceuticals. Predicting photostability and photoreactions in peptides and proteins remains challenging and requires more empirical studies in which powerful UV sources, such as femtosecond lasers, could be an advantage to use.…”
Section: Introductionmentioning
confidence: 99%
“…Third, significant oxidation of tryptophan, methionine and cysteine residues have been observed when passed through the UV diode array detectors (DAD) . It has been shown that the oxidation was mediated by hydroxyl free radicals produced by water molecules in the mobile phase upon UV (especially below 210 nm) irradiation in the DAD.…”
Section: Pitfalls Of Peptide Characterization Using Lc–msmentioning
confidence: 99%